Minang Kabau Wedding Traditions: An Anthropolinguistic Study - irhamni, Mutia (PT. Anagata Sembagi Education, 2024)
The traditions of the Minang Kabau traditional wedding ceremony have cultural meanings and sociological functions that are followed from generation to generation by the Minang Kabau community. However, these traditions are not fully held by the community due to the shift of non-matrilineal culture. This study aims to explain the wedding ceremony traditions of the Minang Kabau tribe in matrilineal cultural practices. This research uses anthropological theory, where data is taken through the method of interviews (open-ended interviews), observation (observation) both participatory observation and observation-periodic to the field, and literature review (written document) This research uses qualitative methods. The data obtained were 10 people who helped implement the wedding ceremony traditions of the Minang Kabau tribe. From this research, descriptive data and explanations can be presented from the traditional wedding traditions of the Minang Kabau.The local wisdom contained in the traditional wedding traditions of the Minang Kabau is consensus in achieving goals, mutual cooperation, mutual honor between the two families and the bride and groom.